Composição e estrutura da vegetação ripária na sub-bacia do córrego do Cintra (Botucatu-SP) - Belluta, Ivalde [UNESP]; Valente, José Pedro Serra [UNESP]; Carvalho, Lídia Raquel de [UNESP]; Silva, Assunta Maria Marques da [UNESP]; Engel, Vera Lex [UNESP] (My University, 2014)
Basaltic Cuestas are located in the middle-west landscapes of São Paulo state and are characterized by Semideciduous Forest. The aim of this study was to characterize the structure, the successional stage and the diversity of the riparian forest of the Cintra stream sub-watershed, located at the region of Botucatu Cuesta. The phytosociological method applied to the three areas was the point-quarter, respectively > 5 m and < 5 m of height. The Friedman test was adopted in the comparison among tree species in all three areas and was followed by Dunn’s test, at 5% significance. The analyzed indexes were relative dominance − (DoR), relative density − (DR), and covering index − (IVC), obtained by means of an electronic spreadsheet; the successional stage was determined by the relative proportion among the numbers of individuals of different synusiae species identified; and the diversity of species was studied based on the diversity indexes of Shannon-Wiener (H’), Pielou (J) and Simpson, connotation 1-D, using the software Past. In the three sampling areas, 2,241 arboreal individuals of 145 species were found, which belong to 55 botanical families, and the most representative families were Fabaceae, 16.3%; Lauraceae, Myrtaceae and Boraginaceae, 7% each, totaling 37.3% of the total sampling. The species with the highest DoR, DR and IVC in areas 1, 2 and 3, respectively, were Calophyllum brasiliense, Piptadenia gonoacantha and Gochnatia polymorpha. The successional stage in area 1 was considered late, in area 2 was intermediate, and the one in area 3 was pioneer, while the diversity (H’A1 = 4.08; H’A2 = 3.79; H’A3 = 3.31 nats/ind-1) of species was considered high and with good equitability for all 3 areas. Therefore, the indexes indicated greater dominance of a few species in area 3, which is in succession process, requiring reforestation and forest regeneration.

As Cuestas Basálticas apresentam-se na paisagem da região central do Estado de São Paulo e caracterizam-se pela Floresta Estacional Semidecidual. O objetivo deste trabalho foi caracterizar a estrutura, estádio sucessional e a diversidade da mata ripária integrante da sub-bacia do córrego do Cintra, situada na região da Cuesta de Botucatu. O método fitossociológico utilizado em três áreas foi o de ponto-quadrante com dois indivíduos amostrados em cada quadrante e de tamanho > 5 m e < 5 m de altura. Foi utilizado o teste de Friedman na comparação das espécies arbóreas nas três áreas, seguido do teste de Dunn, ao nível de 5% de significância. Os índices analisados foram dominância relativa − DoR, densidade relativa − DR, e índice de valor de cobertura − IVC, obtidos através de cálculo em planilha eletrônica; o estádio sucessional foi determinado pela proporção relativa entre os números de indivíduos de espécies de diferentes sinúsias identificadas; a diversidade de espécies foi estudada com base nos índices de diversidade de Shannon-Wiener (H’), Pielou (J) e Simpson, conotação 1-D, através do programa Past. Nas três áreas de amostragem foram encontradas 2.241 indivíduos arbóreos de 145 espécies, pertencentes a 55 famílias botânicas, sendo as mais representativas Fabaceae com 16,3%; Lauraceae, Myrtaceae e Boraginaceae com 7% cada, totalizando 37,3% da amostragem total. As espécies com maior DoR, DR e IVC nas áreas 1, 2 e 3 respectivamente foram Calophyllum brasiliense, Piptadenia gonoacantha e Gochnatia polymorpha. O estádio sucessional na área 1 foi considerado mais tardio, na área 2 intermediário, e pioneiro na área 3, além da diversidade (H’A1 = 4,08; H’A2 = 3,79; H’A3 = 3,31 nats/ind-1) das espécies, que foi considerada alta e boa equabilidade nas três áreas. Portanto, na área 3 os índices indicaram maior dominância de poucas espécies que está em processo de sucessão, com a necessidade de revegetação e regeneração florestal.
Composition and structure of the riparian forest in the sub-watershed of Cintra stream (Botucatu-SP)
Keywords: Riparian forest; Floristics; Successional stage; Diversity; Catchment; Mata ripária; Florística; Estádio sucessional; Diversidade; Sub-bacia hidrográfica